Legal protection for consumers whose certificates are collateralized by the developer - Johanes Rodo Mulia; Eko Wahyudi (Jurnal Cakrawala Hukum, 2022)
This study analyzes the Consumer Protection law in adequately protecting home buyers at Violet Garden, Bekasi. These consumers are faced with losing their house certificates because they have guaranteed them to a non-pawnbroker bank (Maybank). Finally, the Central Jakarta Commercial Court ruled that the developer was bankrupt because he was unable to pay his debts. The curator invites the buyer to participate in paying off the developer's debt, which amounts to approximately fifty percent of the purchase price. This investigation uses a normative juridical approach, namely a truth-seeking procedure based on the logic of legal studies from a normative point of view. The results of this study are that banks must protect consumer rights and not cause problems that result in material losses experienced by consumers. Consumers can file lawsuits because the parties responsible for this case are PT Bank Rakyat Indonesia Tbk, PT Bank Tabungan Negara Tbk, and PT Nusuno Karya, and the element of tort has been fulfilled. However, currently, there are no regulations that strictly regulate how a house can be sold by a developer so that the state can protect consumers.How to cite item: Mulia, J., Wahyudi, E. (2022). Legal protection for consumers whose certificates are collateralized by the developer. Jurnal Cakrawala Hukum, 13(3), 281-290. DOI:https://doi.org/10.26905/idjch.v13i3.8389.